The Significance of Risk Management in Ensuring Security of Logistics Processes in Small Service Enterprises - Oziębło, Małgorzata; Szczerbak, Monika (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
This article aims to enhance the current understanding of risk in strategic management, with a specific focus on ensuring security of corporate logistics processes. The research problem was formulated in the form of a question: What is the significance of risk identification in ensuring the security of logistics processes, considering an evaluation of the present state in light of identified gaps, hazards, and the consequences of their occurrence? The following research hypothesis was verified: The identification of risks associated with compromising security of logistics processes in small enterprises has a direct impact on the capacity to manage risk and, consequently, on ensuring the security of these processes in small service enterprises operating within the supply chain.